Association between dietary carotenoid intakes and the risk of heart failure in males and females: a cross-sectional study of NHANES, 2009–2018 - Gao, Juan; Xie, Yan-You; Zang, Yi-Chen; Tan, Kai; Li, Pei-Hui; Yu, Hai-Yang; Lian, Zhe-Xun; Wang, Jian-Xun (Frontiers in Global Women's Health, 2025)
PurposeHeart failure (HF) is a major contributor to morbidity and mortality among males and females worldwide. However, the difference in predisposition, progression, and management of HF between males and females remains underexplored. This study aimed to investigate the association between dietary carotenoid intake and HF using data from a nationally representative sample of adults in the US.Patients and methodsThe National Health and Nutrition Examination Survey was conducted from 2009 to 2018. A total of 22,119 participants (10,519 males and 11,600 females) aged 20–80 years were included in this study. Logistic regression analyses and smooth curve fitting were used to explore the association between carotenoid intake and the risk of HF in males and females.ResultsThe odd ratios with 95% confidence intervals of dietary carotenoid intake for individuals with current HF, after adjusting for confounders in the model were 0.34 (0.13, 0.85; P for trend = 0.016) in females and 1.35 (0.74, 2.44; P for trend = 0.255) in males, comparing the highest to the lowest quartile. Smooth curve fitting suggested that total carotenoid intake was negatively associated with the risk of HF in females. The sex-based difference in this association was statistically significant.ConclusionsHigher dietary carotenoid intake was associated with lower odds of having current HF in US females but not in males. However, this was a cross-sectional study, no causal relationship could be drawn, and the results should be interpreted with caution.